Debunking Occam's razor: Diagnosing multiple genetic diseases in families by whole‐exome sequencing. Issue 3 (13th March 2017) - Balci, T.B.; Hartley, T.; Xi, Y.; Dyment, D.A.; Beaulieu, C.L.; Bernier, F.P.; Dupuis, L.; Horvath, G.A.; Mendoza‐Londono, R.; Prasad, C.; Richer, J.; Yang, X.‐R.; et al.
Abstract : Background: Recent clinical whole exome sequencing (WES) cohorts have identified unanticipated multiple genetic diagnoses in single patients. However, the frequency of multiple genetic diagnoses in families is largely unknown. Aims: We set out to identify the rate of multiple genetic diagnoses in probands and their families referred for analysis in two national research programs in Canada. Materials & Methods: We retrospectively analyzed WES results for 802 undiagnosed probands referred over the past 5 years in either the FORGE or Care4Rare Canada WES initiatives. Results: Of the 802 probands, 226 (28.2%) were diagnosed based on mutations in known disease genes. Eight (3.5%) had two or more genetic diagnoses explaining their clinical phenotype, a rate in keeping with the large published studies (average 4.3%; 1.4 ‐ 7.2%). Seven of the 8 probands had family members with one or more of the molecularly diagnosed diseases. Consanguinity and multisystem disease appeared to increase the likelihood of multiple genetic diagnoses in a family. Conclusion: Our findings highlight the importance of comprehensive clinical phenotyping of family members to ultimately provide accurate genetic counseling. Abstract :